Framing of Israel’s Attack on Doha in Al Jazeera and Al Khaleej: A Robert Entman Perspective - Rifki Mustofa; Hanania Hanum Sa’baniyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The escalating geopolitical tensions in the Middle East, particularly Israel’s attack on Doha, Qatar, on 9 September 2025, received extensive coverage from Al Jazeera and Al Khaleej. This study aims to examine how both media outlets framed and narrated the event using Robert Entman’s framing analysis model. This research adopts a qualitative descriptive approach. The findings reveal that Al Jazeera framed Israel’s attack not merely as a military action but as part of a broader hegemonic project and strategy of regional domination. The causes of the aggression were portrayed as Israel’s expansionist efforts to reshape the regional security structure. The moral evaluation emphasized violations of sovereignty and regional stability, accompanied by recommendations advocating regional political consolidation and the establishment of a new security order. Meanwhile, Al Khaleej framed the attack as a serious violation of Qatar’s sovereignty and highlighted its causes as a deliberate criminal act planned by Israel to target Hamas leaders. Its moral judgment condemned the aggression as a violation of international law and a threat to civilian safety. The proposed recommendations focused on Qatar’s diplomatic assertiveness and the enhancement of security preparedness. This study contributes to media framing scholarship within the context of Middle Eastern geopolitics and enriches the application of Entman’s model in international news analysis.